Penataan Kawasan Obyek Wisata Pantai Watu Maladong Kecamatan Kodi Balaghar Kabupaten Sumba Barat Daya - Sa’diyah, Chalimatus (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Watu Maladong Beach, located in Penengge Ede Village, Kodi Balaghar District, Southwest Sumba Regency, has begun to receive attention from the local government as a tourist destination. It is approximately 57 kilometers from the city center of Tambolaka. This study aims to identify the tourism potential of Watu Maladong Beach based on its attractions and to formulate an area arrangement that is in accordance with this potential. To achieve this goal, qualitative and quantitative descriptive methods are used, including analysis of potential tourist attractions and formulation of area arrangement according to its physical characteristics and attractions. The results of the analysis show that Watu Maladong Beach has significant potential to be developed as a tourist destination, especially in terms of its natural attractions. The natural beauty and natural conditions of this area greatly support the development of tourism activities. However, this area requires special handling for beach facilities in order to cope with the increase in visitor flow during certain periods. Based on its physical characteristics, the area arrangement is divided into three zones: marine tourism zone, historical tourism zone, and outbound zone. In developing the tourism potential of Watu Maladong Beach, it is important to consider ecological aspects so that the balance of the environment and nature is maintained. The local government is expected to create policies that can be used as references and guidelines in developing this area.